2011 Triennial Surveillance Review : External Commentary. (Policy Papers; Policy Paper ;, 2011)
Commentary prepared by Joseph E. Stiglitz, University Professor, Columbia University: Surveillance has widely been viewed as a key instrument by which the IMF ensures member states adhere to the kinds of policies which promote global economic stability and through which the global macroeconomic coordination necessary for economic stability is achieved. Indeed, as Ocampo (2011) notes, "...the first objective of this institution is to provide 'the machinery for consultation and collaboration on international monetary problems.'" But there is also widespread agreement that there are major shortfalls in the achievement of these lofty objectives. Part of the problem has been in the view that countries-particularly those not borrowing from the fund-lack incentives to comply with the advice that would achieve such stability. Since those countries include virtually all of the systemically significant countries, if surveillance has an impact on global stability (as opposed to the well-being of particular countries) it is only the result of (i) a process of consensus building in which actions which they might previously have thought to not be in their interest were in fact in their national interest; or (ii) enough small countries, each of which is systemically insignificant, are affected in a meaningful enough way so as to have systemically significant effects.